MODEL KARAKTERISTIK DAN PERANAN PEKERJA INFORMAL DI KOTA PADANG - Erni Febrina Harahap (Jurnal Apresiasi Ekonomi, 2016)
phenomenon, but as a reality of economythat important in the development of society and national economy. At least, when the government was not quit competence to provide the employment opportunities for the labor force, the informal sector with all its shortage took a role as a container and alternative employment opportunities for the job seekers. It is also experienced by Padang after the earthquake in 2009 which destroyed some facilities and infrastructure as well as at the same time the economic crisis made people involuntarily unemployed and temporarily mitigated by the availability of employment opportunities in the informal sector in urban areas reflected by street vendors as the main face.This study examines and analyzes in depth the characteristics of informal workers to identificate of demographics , region of origin, age of business , hours of operation, capital and finance, health of workers, the problems and their prospects. The methodology used was qualitative descriptive analysis with random data sample of 255 street vendors.The results of the study found that the role of women more prominent than men to work in this sector , and the educational level of workers with family members was not so much different that was only until the equivalent of high school , and workers in the sector was dominated by local residence , with the capital beginning most dominant of ≤ two million, and capable to give experience with lower cost. Keywords : informal workers, business types, roles, education, prospects